The legislation regulating the activities of juvenile courts in Kazakhstan - Mutubayeva, D.M.; Kozhakhmetov, G.Z. (Bulletin of the Karaganda University “Law Series”, 2019)
The article considers the specifics of the application of the legislation regulating the activities of juvenile courts of Kazakhstan, in accordance with international standards in the resolution of family disputes. The analysis of the application of civil law in civil cases of this disputes category, if the property and personal non-property relations between family members are not regulated by the marriage and family legislation of Kazakhstan. And the possibility of applying the rules of marriage and family and (or) civil legislation of the Republic of Kazakhstan, regulating similar relations (analogy of the law). The modern period is characterized by a change in the place of family law in the system of law of the Republic of Kazakhstan and a change in its ideology. In conclusion, marriage and family law is the basis for the protection of the rights and interests of children, parents and the family as a whole, regulating disputes arising from marriage and family relations.